My beef with meat : the healthiest argument for eating a plant-strong diet plus 140 new Engine 2 recipes - Esselstyn, Rip (Grand Central Life & Style, 2013)
"For the millions who are following a plant-based diet, as well as those meat-eaters who are considering it, MY BEEF WITH MEAT is the definitive guide to convincing all that it's truly the best way to eat! New York Times Bestelling author of The Engine 2 Diet and nutrition lecturer Rip Esselstyn, is back and ready to arm readers with the knowledge they need to win any argument with those who doubt the health benefits of a plant-based diet--and convince curious carnivores to change their diets once and for all. Esselstyn reveals information on the foods that most people believe are healthy, yet that scientific research shows are not. Some foods, in fact, he deems so destructive they deserve a warning label. Want to prevent heart attacks, stroke, cancer and Alzheimer's? Then learn the facts and gain the knowledge to convince those skeptics that they are misinformed about plant-base diets, for instance: You don't need meat and dairy to have strong bones or get enough protein You get enough calcium and iron in plants The myth of the Mediterranean diet There is a serious problem with the Paleo diet If you eat plants, you lose weight and feel great MY BEEF WITH MEAT proves the Engine 2 way of eating can optimize health and ultimately save lives and includes more than 145 delicious recipes to help readers reach that goal"--